The efficiency of legal provision on polygamy in Malaysia, critical analysis from Qur'anic perspective - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (International Journal of Contemporary Applied Sciences (IJCAS), 2015)

(untitled)
Islam permits polygamy to preserve women’s dignity and to safeguard the social, moral and economic well-being of wives and their children. Unfortunately, a number of polygamous marriages among Muslims in Malaysia registered at the local ‘Shariah Courts’ are problematic and “misleading” as they do not reflect the teachings of Islam and its Sharīʿah intents on polygamy. As a consequence, polygamy has become a very controversial issue among its critics and supporters. It has invited serious criticisms on the credibility of the legal provision namely Islamic Family Law Act 1984 (IFLA) in curbing the abuse of polygamy. As a short term measure to overcome the problem, it has been suggested that IFLA should be reformed in order to address the current problems faced by Muslims. The IFLA has been amended twice, in 1994 and 2005, and yet the Act has not been gazetted, as some states in Malaysia are not ready to enforce the new enactment due to certain restricting provisions, which according to them are not fully compliant with the true intents of polygamy as stated in the Qur’an and Sunnah. This paper seeks to examine the efficiency of the current provision, and the compatibility between the law of polygamy in the Islamic Family Law Act 1984 with the revelation of Allah (SWT) in the Qur’an and Sunnah of the Prophet (PBUH. It will focus its analysis on the textual sources (nuṣūṣ) of IFLA provisions on polygamy, as well as the effectiveness and the compatibility of the provisions with the sources. The paper comes with recommendations to improve the current provisions on polygamy so that it may not be abused or misused for objectives contrary to its original Sharīʿah intents.